Mirtazapine Induced Bipedal Edema: A Case Report - Amatya, Richa; Kunwar, Dipak; Shrestha, Barsha; Khadka, Subeskshya; Risal, Ajay (Annapurna Journal of Health Sciences, 2023)
Mirtazapine is a commonly used antidepressant which works via alpha-2 adrenergic antagonism to enhance noradrenergic and serotonergic neurotransmission. There is only dearth of literature to suggest the link between mirtazapine use and development of peripheral edema. With this article, we aim to discuss the probability of peripheral edema during the treatment course of mirtazapine. This is among the handful of cases reported describing the probability of peripheral edema due to mirtazapine. Thus, it will be of utmost use to the prescribing physician.